Nutritional strategies to optimize growth performance in nursery pigs - Arroyave Jaramillo, Julian (My University, 2025)
Optimizing dietary strategies in pigs is crucial to enhance growth performance, nutrient utilization, and economic efficiency while minimizing environmental impact. A total of nine experiments (5,423 pigs) and a meta-regression analysis structured in 5 chapters were used to evaluate the effect of Zn levels and sources under different formulation strategies, nursery feed budgets, and a functional fiber ingredient on growth performance, fecal dry matter (DM), mineral excretion, and economic outcomes. In chapter 1, a meta-regression analysis utilizing data from 51 published papers was conducted to identify dietary factors associated with Zn excretion in pigs and develop predictive models for Zn excretion. Principal component analysis indicated that nutrient intake variables, including minerals, fiber, nitrogen, as well as body weight and feed intake, accounted for a significant portion of the variability in Zn excretion. Overall, Zn intake was the primary determinant of fecal Zn excretion, with meta-regression models predicting that 61% of Zn intake is excreted when diets meet the requirement and up to 82% when Zn exceeds requirement estimates. In Chapter 2, two experiments utilizing 2,268 pigs were conducted to evaluate the effects of Zn source (ZnO, Zn hydroxychloride, ZnSO₄, or chelated Zn) and inclusion level on growth performance, fecal DM, fecal Zn concentration, and carcass characteristics. In nursery pigs, increasing dietary Zn led to higher fecal Zn concentrations independent of the Zn source, although overall growth performance and fecal DM were unaffected by Zn source or level. In finishing pigs, Zn source did not affect growth performance, carcass weight, or carcass yield, with only marginal effects observed on backfat depth and lean percentage in favor of Zn hydroxychloride. Chapter 3 utilized 360 nursery pigs to evaluate the impact of dietary acid-binding capacity to pH 4 (ABC-4) and Zn levels on growth performance, fecal DM, and Zn excretion. At the same dietary Zn concentration, low ABC-4 diets enhanced Zn absorption, apparent total tract digestibility of Zn, and fecal DM at early stages, although overall growth performance was not significantly affected by dietary ABC-4. Increasing Zn in low ABC-4 diets improved ADG and ADFI during the experimental period; however, these differences did not translate into a better overall performance. Furthermore, d 24 fecal Zn excretion and serum Zn concentration increased with dietary Zn, validating the results from chapter 1, where the main determinant of fecal Zn excretion was the dietary Zn concentration. Chapter 4 was composed of two experiments that utilized a total of 1,800 pigs to evaluate the effect of nursery feed budget on growth performance and economics. Experiment 1, which was conducted in university research facilities, demonstrated that reducing the budget of complex phase 1 and 2 diets did not affect overall pig performance but improved economic outputs. To confirm these findings, a second experiment was conducted in a commercial research facility. While pigs provided a reduced feed allowance and less complex diets tended to grow slower in the early nursery period, no differences in growth performance were observed by d 63 after weaning. Collectively, these findings suggest that reducing early nursery feed budgets could be a strategy to improve economic outcomes without compromising long-term pig growth. Chapter 5 was composed of three experiments utilizing a total of 995 pigs to evaluate the effect of ValoproWin (VLPW), a functional fiber ingredient composed primarily of insoluble, poorly fermentable fiber, on growth performance and fecal DM in nursery pigs. Within three experiments, sub-objectives were to determine how the response was impacted by: (1) VLPW feeding duration and dietary ABC-4; (2) VLPW inclusion level; and (3) potential interactions between VLPW inclusion level and dietary formulation strategies (nutrient dilution vs. nutrient adjustment). Considering the results of the three experiments collectively, the inclusion of VLPW had minimal effects on growth performance; however, it may serve as a nutritional strategy to promote intestinal health and increase fecal DM.
Keywords: Economics; Feed budgets; Fiber; Performance; Pigs; Zinc